Some social and economic aspects of housing?an international comparison - O hUiginn, P. (Statistical and Social Inquiry Society of Ireland, 1960)
There are two points to be borne in mind in connection with the comparisons made in this paper. The first is that all comparisons based on international statistics are affected by the reliability and comparability of the different sets of figures and any conclusion drawn must, therefore, be regarded with reservation. On the other hand, a fair degree of comparability has now been achieved in the statistics used in this paper so that, in general, it may be taken that the comparisons made tend to give a picture of the actual situation which is broadly correct. Where necessary, attention is drawn here and there in connection with particular sets of figures to any known defect in comparability.
Read before the Society, 27 November 1959
Keywords: Social housing; Housing markets; Irish housing; Housing demand; Housing supply; 314.15